Civil Society, Cultural Hegemony, and Citizenship: Implications for Adult Educators - Pat Durish; Rachel Gorman; Morrell Shahrzad; Daniel Schugurensky; Deborah Sword (Adult Education Research Conference, 1999)
The participants in this symposium provide a panorama of positions about civil society, citizenship and the dynamics of the exercise of power in the world of adult education. Theoretical approaches range from postmodernism to cultural studies to Marxist and critical theoretical positions. Case studies are equally diverse, ranging from North and Latin America to the Middle East.